Implikasi Ambiguitas Kreditur Separatis Dan Kurator Dalam Pembagian Boedel Debitor Pailit Menurut Perspektif Philosophy - Ronald Saija; Iming Maknaan Tesalonika; Herman Bakir (Pattimura Legal Journal)
Introduction: Completing debt and receivables agreements with serious material security objects between creditors and debtors through the Bankruptcy route. Bankruptcy as a form of dispute resolution regulated in Articles 749-910 of Wetboek van Koophandel which has been codified through Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations.